THE EFFECT OF WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY IN GARUT REGENCY - Pertiwi, Dinda Yuliawati; Awaliyah, Septiani Nurdina; Nuradilah, Tania; Ramdania, Devia (Jurnal Administrasi Negara, 2025)
This research was prompted by the suboptimal work environment issues in Garut Regency, which have led to low employee productivity. The purpose of this research is to determine the effect of the work environment on employee productivity and to identify the aspects of the work environment that contribute the most. This research uses a quantitative approach with a survey method, involving 50 respondents working in various business sectors in Garut Regency. Data was collected through a closed-ended questionnaire designed based on indicators of the work environment and productivity, and then analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The results of the research show that the work environment has a positive effect on employee productivity, both from physical aspects, such as lighting, temperature, and workspace comfort, and non-physical aspects, such as social relationships, communication, and support from superiors. These findings confirm that a conducive work environment can improve overall employee motivation and performance. In conclusion, increased employee productivity can be achieved by creating a physically comfortable and psychologically supportive work environment. Therefore, companies and government agencies in Garut Regency need to develop integrated work environment management strategies to create a healthy, harmonious, and productive workplace.